The Implementation of Halal Slaughterhouse in the Perspective of Talcott Parson's Functional Structural Theory - Hikmatul Hasanah; Agung Suwandaru (ADP Publisher, 2023)
Large-scale slaughterhouses and meat producers catering to the broader community as consumers bear the ongoing responsibility of ensuring the sustainability of their businesses. Consequently, continuous structural and functional improvements must be prioritized to foster trust, safety, and comfort within the wider community. The halal abattoir operates as an